Studi Fasies Formasi Endapan Danau Untuk Menentukan Lingkungan Pengendapan Danau Limboto - Abd Kadir Mubarak A Amin; Yayu Indriati Arifin; Noviar Akase (Jambura Geoscience Review, 2019)
The research area located in the lowland zone and the corrugated hilly zone which is dominated by sedimentary rocks. Therefore, this study aims to determine the geological features of the research area and the study of depositional environmental facies of the Lake Deposits Formation as an analysis of the depositional environment of Limboto Lake. The research method used is the surface geological mapping, measuring a section of stratigraphic and laboratory analysis. Field data consists of stratigraphical features of the research area. Laboratory analysis consists of petrography and stratigraphy-sedimentology analysis. It can be concluded facies and stratigraphy of research from older to youngest, consists of clastic limestones unit formed in Late Miocene-late Early Pliocene age, reef limestones formed in Late Miocene-early Late Pliocene age, sandstones unit formed in Late Pliocene-Pleistocene age, clay unit, and sandy clay unit are deposited in Holocene. Overall the study site consisted of marine, transitional and terrestrial deposition environment with Lake Deposits Formation facies is lake margin clastic deposits and meandering-stream environment deposits.